EVALUASI DESA PEMEKARAN - Pirdo Mangatur MS; M.Y. Tiyas Tinov (Jurnal Kebijakan Publik, 2013)
This research relate to countryside evaluation of pemekaranin Kecamatan Rambah Samo Kabupaten Rokan Hulu; as a mean to analyse fluency management ofgovernance of utilizable countryside, and also service fluency to society to reach improvement,growth, and progress of development. This research use method research of survey with descriptivequantitative approach, and also obtained data of taken away from sampel is population, namely[done/conducted] research at small and also big population, but data studied by data of taken awayfrom sampel is population, so that found by events relative, relations and distribution betweenvariable. Whereas data collecting technique that is by observation, interview, and enquette. Resultof research and solution of data analysis concerning evaluation countryside known that policy ofpemekaran of implementation countryside have better by government. This matter seen fromresponder comments of countryside evaluation pemekaran of mean enter at good category.